Assessing willingness to pay for information delivery among rural women in Ghana - Kwapong, T.F.O.A. (International Journal of Emerging Technologies in Learning 2(4): 70 - 76, 2007)
This study used rural household survey data collected from 1000 female household heads randomly selected from all the ten administrative regions in Ghana to examine rural women’s willingness to pay for information delivered via three technologies – community radio, private radio, and extension agents. A contingent valuation method was used for the study. Household expenditures, household education, and membership in community organizations emerged as the principal factors influencing rural women’s willingness to pay for the various information technologies. This point to the need to cast rural empowerment policies and programs within the broader poverty reduction policies of government.
Keywords: Education; Empowerment; Extension; Income; Information communication technology; Radio; rural; Women